Postracial fantasies, blackness, and zombies - King Watts, Eric (Communication and critical/cultural studies, 2017)
The essay mainly performs a structural and formal analysis of the logics and affective economies of postracial fantasies so as to eventually offer the Zombie trope as a mode of analysis figuring alternative ways of thinking race relations. The essay contends that the Zombie, when articulated with discourses and feelings of the postracial, signifies the unleashing of black bio-threat bodies upon a population; and that enjoyment of the postracial and the Zombie Apocalyptic genre obscures and resuscitates this signification. As a brief case study, the essay discusses the display, materiality, and "bloody" enjoyment of the "Zombie Obama" target mannequin by gun enthusiasts and preppers.